PEMANFAATAN GETAH BIDURI DALAM PRODUKSI ALBUMIN IKAN GABUS (Ophiocephalus striatus) - Ita Mustrini; Mappiratu Mappiratu; Nurakhirawati Nurakhirawati (KOVALEN: Jurnal Riset Kimia, 2016)
The Research about utilization of sap Biduri in the production of albumin fish cork (Ophiocephalus striatus). Has been done This research  purposes to determine the ratio of sap Biduri to extract cork fish that produce the protein albumin with the highest yield and optimum heating time which produces the highest yield of the protein albumin. The study used a completely randomized design (CRD), which consists of the influence of the ratio of sap Biduri to extract protein and the effect of heating time Biduri to extract latex mixture. Each treatment is done twice to obtain 22 units of the experiment. The highest protein yield was obtained at a ratio of sap Biduri 3,0 : 30 and the heating time of 60 minutes at 53,43 %. The purity of the highest degree obtained at the optimum 50 minutes warm up period of 35.50 %.Keywords : Fish Cork, Biduri Protease enzyme, Protein yield of albumin, Albumin purity degree